PENGENALAN TEKNOLOGI VIRTUAL REALITY (VR) PADA PEMBELAJARAN SIMULASI PEMBUATAN KOMPUTER DI JURUSAN TEKNIK INFORMASI DAN JARINGAN (TKJ) - Andy Satria; Surya Inra Simbolon; Fidelis Sitinjak (Jurnal Ilmiah Teknik, 2023)
The study is motivated by the difficulties encountered in the learning process of computer assembly. Inadequate support for the learning process arises from the insufficient availability of hardware components corresponding to the student population, leading to challenges for students in understanding and applying the subject matter. The shortage of components is primarily due to budget constraints for procurement, resulting in damage to school visual aids caused by errors made by students during practical exercises. Hence, there is a necessity to develop computer assembly learning materials incorporating virtual reality technology. The research utilized the Research and Development (R&D) four-D (4D) development model, consisting of Define, Design, and Develop stages. The multimedia development model applied in this study follows the Luther-Sutopo version, involving six stages: concept, design, material collection, assembly, testing, and distribution. The research integrates both the 4D and Luther-Sutopo versions of the multimedia development model. The outcomes of this investigation include computer assembly learning materials based on virtual reality, presenting explanations of hardware components and a simulation segment for computer assembly. The product validity testing resulted in a score of 0.78, meeting the validity criteria. Regarding practicality, the test outcomes indicated a score of 85.11, demonstrating high practicality. Furthermore, the effectiveness test yielded a score of 0.74, indicating a high level of effectiveness.